The Impact of Corruption in Health Operational Assistance on State Finances - Agusman, Agusman; Haryadi, Slamet (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study examines the misuse of Health Operational Assistance (BOK) at the Ogan Lima Health Center in North Lampung, which has resulted in significant losses for both the state and the community. Utilizing a normative legal approach, this research analyzes the modus operandi of corruption in the management of BOK, including embezzlement of funds and practices of gratification. The findings indicate that the misuse of BOK funds not only leads to financial losses but also creates inequities in access to health services, particularly for the most vulnerable groups in society. Factors contributing to the occurrence of corruption include a lack of oversight, deeply rooted corruption culture, and the personal motivations of the individuals involved. This study recommends strengthening oversight mechanisms, enhancing community participation, and implementing information technology to improve transparency and accountability in the management of BOK. With these measures, it is hoped that the misuse of health funds can be minimized, thereby improving the quality of health services in Indonesia and maintaining public trust in health institutions.